Study of Body Composition and Metabolic Parameters in HIV-1 Male Patients - Gurudath Gundurao Sreekantamurthy; N Biplab Singh; Th Bhimo Singh; Th Suraj Singh; Karam Romeo Singh (Journal of Nutrition and Metabolism)
Background. HIV patients on highly active antiretroviral therapy (HAART) containing protease inhibitors (PIs) had been often associated with lipodystrophy. However, there are only few studies on association of nucleoside and nonnucleoside reverse transcriptase inhibitors (NRTI and NNRTI) with lipodystrophy. Study Design. One hundred and one HIV male patients were categorised into ART naïve (n=22), zidovudine (n=22), stavudine (n=18), tenofovir (n=15), and PIs (n=24) based HAART. Their clinicoepidemiological data had been entered in preformed pro forma. The body composition, using TANITA machine and metabolic parameters like lipid profile, blood sugars was analysed. Results. Clinically, lipoatrophy of face was most prevalent in HIV patients on stavudine (15 patients, 83.3%) and PIs (20 patients, 83.3%) based HAART. The mean BMI among study population was in normal range. Excess visceral fat was most prevalent among patients on PIs, 4 patients (16.7%). The waist-hip ratio was significantly higher in PIs (P=0.01) based HAART. There was no significant difference among different study populations in terms of BMI (P=0.917), body water (P=0.318), body fat (P=0.172), bone mass (P=0.200), and muscle mass (P=0.070). Hypertriglyceridiemia was found in stavudine, tenofovir, and protease inhibitors regimens. Low levels of high density lipoprotein (HDL) was found zidovudine, stavudine, and PIs regimens. Fasting and postprandial hyperglycaemia was found PIs and impaired glucose tolerance in stavudine regimen. Conclusion. Patients on PIs were associated with truncal obesity and lipoatrophy of face, along with dyslipidemia and hyperglycaemia. Stavudine based regimen is associated with hypertriglyceridiemia and low HDL along with lipoatrophy of face.